2011
DOI: 10.1007/s11661-011-0856-z
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Grain Refinement and Amorphization in Ti-10V-2Fe-3Al Alloy

Abstract: The microstructural evolution and grain refinement mechanisms of a Ti-10V-2Fe-3Al alloy, b-solution quenched and cold forged (CF) to strains of 0.1, 0.35, and 1.2 have been investigated using optical microscopy (OM), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The results showed that the stress-induced martensitic transformation became a predominant deformation mode in the metastable Ti-10V-2Fe-3Al alloy during cold forging. These martensites a¢¢ repeatedly divided the original b paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…It is observed that the amount of the stress induced a 00 decreases with increasing strain (completely disappears at the highest equivalent strain applied of 242), consistent with the observations earlier [14][15][16][17]. Although the reverse a 00 to b transformation has been proposed to be responsible [14][15][16][17], the speculated cause -local temperature rise above A s due to SPD -is not justified.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…It is observed that the amount of the stress induced a 00 decreases with increasing strain (completely disappears at the highest equivalent strain applied of 242), consistent with the observations earlier [14][15][16][17]. Although the reverse a 00 to b transformation has been proposed to be responsible [14][15][16][17], the speculated cause -local temperature rise above A s due to SPD -is not justified.…”
Section: Discussionsupporting
confidence: 66%
“…Similar mechanisms of grain refinement were proposed in a Ti-10V-2F e-3Al alloy processed by cold forging to large strains, with the final nano b grains produced by rotational dynamic recrystallisation in the spreading shear bands [17]. The lack of a 00 in the final microstructure, however, prompted the suggestion that local temperature increases to above the so-called austenitic starting temperature (A s ) [13] [14][15][16][17]. Xu et al [14][15][16] believed that dislocation pileups at the a 00 /b interfaces may have resulted in the dissipation of some mechanical energy as heat, leading to a local increase in temperature, whereas Chen et al [17] attributed the temperature rise to the formation of adiabatic shear bands.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations